Phraseological Units' Impact on the English Language (Eurasian Journal of Learning and Academic Teaching, 2023)
This article's main focus is the analysis of English phraseological units, one of the most expressive stylistic forms of language expression. This article examines a variety of values related to the nature and organization of the phonological units that make up language phonological books.